Key Factors Affecting Startups’ Contribution to SDGs for a Sustainable Future: Integrating a Triple Bottom Line (TBL) Theory - Cho, Moon Hwan (Journal of Ecohumanism, 2024)
This paper explores the key factors influencing startups’ contributions to the Sustainable Development Goals (SDGs). Through an extensive literature review, we develop hypotheses concerning these factors. The research framework was developed based on the Triple Bottom Line theory. Using a survey method, we collect quantitative data from startup founders (that is, respondents are startup founders) in South Korea. Our findings highlight the critical role of innovation, stakeholder engagement, resource availability, and regulatory environment in driving startups’ SDG-related activities. The paper concludes with implications for policy and practice, emphasizing the need for supportive ecosystems to enhance startups’ contributions to sustainable development.